CLINICAL, RADIOGRAPHIC, AND MOLECULAR METHODS FOR EARLY DIAGNOSIS OF PERI-IMPLANTITIS - Adilov K.Z., Adilova Sh.T. (Modern World Education: New Age Problems – New solutions, 2026)
Peri-implantitis is a chronic inflammatory disease of peri-implant tissues, characterized by progressive marginal bone loss and the risk of implant failure. Early and accurate diagnosis is essential to ensure timely intervention and improve treatment outcomes. Conventional clinical methods, including probing depth, bleeding on probing, and suppuration, as well as radiographic assessment of bone levels, remain the cornerstone of diagnosis [1,3]. However, recent advances in the analysis of peri-implant crevicular fluid (PICF) biomarkers and molecular technologies enable the detection of pathological processes before clinical manifestations become evident [2,5,6]. Integration of clinical, radiographic, and molecular approaches enhances diagnostic accuracy and facilitates prediction of disease progression.